Method of situational management of operational-service dialogue of regional management - Androshchuk, О. S.; Yegorov, V. S. (Honor and Law, 2019)
The actuality of situational management for fulfilling tasks in the protection of the state border, as well as the concept of knowledge management in solving the problems of situational management is substantiated. The method of situational management with the use of knowledge is developed, which enables to make decisions on the situation in the operational and service activities of the regional administration.